A Coiled-Coil Peptide Shaping Lipid Bilayers upon Fusion. - Rabe, Martin; Aisenbrey, Christopher; Pluhackova, Kristyna; De Wert, Vincent; Boyle, Aimee L.; Bruggeman, Didjay F.; Kirsch, Sonja; Böckmann, Rainer; Kros, Alexander; Raap, Jan; Bechinger, Burkhard (Biophysical Journal, 2016)
A system based on two designed peptides, namely the cationic peptide K, (KIAALKE)3, and its complementary anionic counterpart called peptide E, (EIAALEK)3, has been used as a minimal model for membrane fusion, inspired by SNARE proteins. Although the fact that docking of separate vesicle populations via the formation of a dimeric E/K coiled-coil complex can be rationalized, the reasons for the peptides promoting fusion of vesicles cannot be fully explained. Therefore it is of significant interest to determine how the peptides aid in overcoming energetic barriers during lipid rearrangements leading to fusion. In this study, investigations of the peptides' interactions with neutral PC/PE/cholesterol membranes by fluorescence spectroscopy show that tryptophan-labeled K∗ binds to the membrane (KK∗ ∼6.2 10(3) M(-1)), whereas E∗ remains fully water-solvated. (15)N-NMR spectroscopy, depth-dependent fluorescence quenching, CD-spectroscopy experiments, and MD simulations indicate a helix orientation of K∗ parallel to the membrane surface. Solid-state (31)P-NMR of oriented lipid membranes was used to study the impact of peptide incorporation on lipid headgroup alignment. The membrane-immersed K∗ is found to locally alter the bilayer curvature, accompanied by a change of headgroup orientation relative to the membrane normal and of the lipid composition in the vicinity of the bound peptide. The NMR results were supported by molecular dynamics simulations, which showed that K reorganizes the membrane composition in its vicinity, induces positive membrane curvature, and enhances the lipid tail protrusion probability. These effects are known to be fusion relevant. The combined results support the hypothesis for a twofold role of K in the mechanism of membrane fusion: 1) to bring opposing membranes into close proximity via coiled-coil formation and 2) to destabilize both membranes thereby promoting fusion.

A Critical Comparison of Biomembrane Force Fields: Protein-Lipid Interactions at the Membrane Interface. - Pluhackova, Kristyna; Sandoval Perez, Gloria; Böckmann, Rainer (Journal of Chemical Theory and Computation, 2017)
Molecular dynamics (MD) simulations offer the possibility to study biological processes at high spatial and temporal resolution often not reachable by experiments. Corresponding biomolecular force field parameters have been developed for a wide variety of molecules ranging from inorganic ligands and small organic molecules over proteins and lipids to nucleic acids. Force fields have typically been parameterized and validated on thermodynamic observables and structural characteristics of individual compounds, e.g. of soluble proteins or lipid bilayers. Less strictly, due to the added complexity and missing experimental data to compare to, force fields have hardly been tested on the properties of mixed systems, e.g. on protein-lipid systems. Their selection and combination for mixed system is further complicated by the partially differing parameterization strategies. Additionally, the presence of other compounds in the system may shift the subtle balance of force field parameters. Here, we assessed the protein-lipid interactions as described in the four atomistic force fields GROMOS54a7, CHARMM36, and the two force field combinations Amber14sb/Slipids and Amber14sb/Lipid14. Four observables were compared, focusing on the membrane-water interface: the conservation of the secondary structure of transmembrane proteins, the positioning of a transmembrane peptide relative to the lipid bilayer, the insertion depths of side chains of unfolded peptides absorbed at the membrane interface, and the ability to reproduce experimental insertion energies of Wimley-White peptides at the membrane interface. Significant differences between the force fields were observed that affect e.g. membrane insertion depth and tilting of transmembrane peptides.

A Critical Comparison of Biomembrane Force Fields: Structure and Dynamics of Model DMPC, POPC, and POPE Bilayers. - Pluhackova, Kristyna; Kirsch, Sonja; Han, Jing; Sun, Liping; Jiang, Zhenyan; Unruh, Tobias; Böckmann, Rainer (Journal of Physical Chemistry B, 2016)
Atomistic molecular dynamics simulations have become an important source of information for the structure and dynamics of biomembranes at molecular detail difficult to access in experiments. A number of force fields for lipid membrane simulations have been derived in the past; the choice of the most suitable force field is, however, frequently hampered by the availability of parameters for specific lipids. Additionally, the comparison of different quantities among force fields is often aggravated by varying simulation parameters. Here, we compare four atomistic lipid force fields, namely, the united-atom GROMOS54a7 and the all-atom force fields CHARMM36, Slipids, and Lipid14, for a broad range of structural and dynamical properties of saturated and monounsaturated phosphatidylcholine bilayers (DMPC and POPC) as well as for monounsaturated phosphatidylethanolamine bilayers (POPE). Additionally, the ability of the different force fields to describe the gel-liquid crystalline phase transition is compared and their computational efficiency estimated. Moreover, membrane properties like the water flux across the lipid bilayer and lipid acyl chain protrusion probabilities are compared.

Binding Characteristics of Sphingosine-1-Phosphate to ApoM hints to Assisted Release Mechanism via the ApoM Calyx-Opening. - Zhang, Hansi; Pluhackova, Kristyna; Jiang, Zhenyan; Böckmann, Rainer (Scientific Reports, 2016)
Sphingosine-1-phosphate (S1P) is a lysophospholipid mediator carried by the HDL-associated apoM protein in blood, regulating many physiological processes by activating the G protein-coupled S1P receptor in mammals. Despite the solved crystal structure of the apoM-S1P complex, the mechanism of S1P release from apoM as a part of the S1P pathway is unknown. Here, the dynamics of the wild type apoM-S1P complex as well as of mutants were investigated by means of atomistic molecular dynamics simulations. The potential of mean force for S1P unbinding from apoM reflected a large binding strength of more than 60 kJ/mol. This high unbinding free energy for S1P underlines the observed specificity of the physiological effects of S1P as it suggests that the spontaneous release of S1P from apoM is unlikely. Instead, S1P release and thus the control of this bioactive lipid probably requires the tight interaction with other molecules, e.g. with the S1P receptor. Mutations of specific S1P anchoring residues of apoM decreased the energetic barrier by up to 20 kJ/mol. Moreover, the ligand-free apoM protein is shown to adopt a more open upper hydrophilic binding pocket and to result in complete closure of the lower hydrophobic cavity, suggesting a mechanism for adjusting the gate for ligand access.

Biomembranes in atomistic and coarse-grained simulations - Pluhackova, Kristyna; Böckmann, Rainer (Journal of Physics: Condensed Matter, 2015)
The architecture of biological membranes is tightly coupled to the localization, organization, and function of membrane proteins. The organelle-specific distribution of lipids allows for the formation of functional microdomains (also called rafts) that facilitate the segregation and aggregation of membrane proteins and thus shape their function. Molecular dynamics simulations enable to directly access the formation, structure, and dynamics of membrane microdomains at the molecular scale and the specific interactions among lipids and proteins on timescales from picoseconds to microseconds. This review focuses on the latest developments of biomembrane force fields for both atomistic and coarse-grained molecular dynamics (MD) simulations, and the different levels of coarsening of biomolecular structures. It also briefly introduces scale-bridging methods applicable to biomembrane studies, and highlights selected recent applications.
Keywords: biomembranes; coarse-grained simulation; membranes; molecular dynamics simulation; multiscale modeling; resolution transformation

Closely related, yet unique: Distinct homo- and heterodimerization patterns of G protein coupled chemokine receptors and their fine-tuning by cholesterol. - Gahbauer, Stefan; Pluhackova, Kristyna; Böckmann, Rainer (PLoS Computational Biology, 2018)
Chemokine receptors, a subclass of G protein coupled receptors (GPCRs), play essential roles in the human immune system, they are involved in cancer metastasis as well as in HIV-infection. A plethora of studies show that homo- and heterodimers or even higher order oligomers of the chemokine receptors CXCR4, CCR5, and CCR2 modulate receptor function. In addition, membrane cholesterol affects chemokine receptor activity. However, structural information about homo- and heterodimers formed by chemokine receptors and their interplay with cholesterol is limited. Here, we report homo- and heterodimer configurations of the chemokine receptors CXCR4, CCR5, and CCR2 at atomistic detail, as obtained from thousands of molecular dynamics simulations. The observed homodimerization patterns were similar for the closely related CC chemokine receptors, yet they differed significantly between the CC receptors and CXCR4. Despite their high sequence identity, cholesterol modulated the CC homodimer interfaces in a subtype-specific manner. Chemokine receptor heterodimers display distinct dimerization patterns for CXCR4/CCR5 and CXCR4/CCR2. Furthermore, associations between CXCR4 and CCR5 reveal an increased cholesterol-sensitivity as compared to CXCR4/CCR2 heterodimerization patterns. This work provides a first comprehensive structural overview over the complex interaction network between chemokine receptors and indicates how heterodimerization and the interaction with the membrane environment diversifies the function of closely related GPCR

Dynamic Cholesterol-Conditioned Dimerization of the G Protein Coupled Chemokine Receptor Type 4. - Pluhackova, Kristyna; Gahbauer, Stefan; Kranz, Franziska; Wassenaar, Tsjerk; Böckmann, Rainer (PLoS Computational Biology, 2016)
G protein coupled receptors (GPCRs) allow for the transmission of signals across biological membranes. For a number of GPCRs, this signaling was shown to be coupled to prior dimerization of the receptor. The chemokine receptor type 4 (CXCR4) was reported before to form dimers and their functionality was shown to depend on membrane cholesterol. Here, we address the dimerization pattern of CXCR4 in pure phospholipid bilayers and in cholesterol-rich membranes. Using ensembles of molecular dynamics simulations, we show that CXCR4 dimerizes promiscuously in phospholipid membranes. Addition of cholesterol dramatically affects the dimerization pattern: cholesterol binding largely abolishes the preferred dimer motif observed for pure phospholipid bilayers formed mainly by transmembrane helices 1 and 7 (TM1/TM5-7) at the dimer interface. In turn, the symmetric TM3,4/TM3,4 interface is enabled first by intercalating cholesterol molecules. These data provide a molecular basis for the modulation of GPCR activity by its lipid environment.

Dynamic processes in biological membrane mimics revealed by quasielastic neutron scattering. - Lautner, Lisa; Pluhackova, Kristyna; Barth, Nicolai; Seydel, Tilo; Lohstroh, Wiebke; Böckmann, Rainer; Unruh, Tobias (Chemistry and physics of lipids, 2017)
Neutron scattering is a powerful tool to study relaxation processes in biological membrane mimics in space and time. Combining different inelastic and quasielastic neutron scattering techniques, a large dynamic range can be covered: from atomic to mesoscopic lengths and from femto- to some hundreds of nanoseconds in time. This allows studies on e.g. the diffusion of lipids, the membrane undulation motions, the dispersion of sound waves in membranes as well as the mutual interactions of membrane constituents such as lipids, proteins, and additives. In particular, neutron scattering provides a quite direct experimental approach to the inter-atomic and inter-molecular potentials on length and time scales which are perfectly accessible by molecular dynamics (MD) simulations. Neutron scattering experiments may thus substantially support the further refinement of biomolecular force fields for MD simulations by supplying structural and dynamical information with high spatial and temporal resolution. In turn, MD simulations support the interpretation of neutron scattering data. The combination of both, neutron scattering experiments and MD simulations, yields an unprecedented insight into the molecular interactions governing the structure and dynamics of biological membranes. This review provides an overview of the molecular dynamics in biological membrane mimics as revealed by neutron scattering. It focuses on the latest findings such as the fundamental molecular mechanism of lateral lipid diffusion as well as the influence of additives and proteins on the short-time dynamics of lipids. Special emphasis is placed on the comparison of recent neutron scattering and MD simulation data with respect to molecular membrane dynamics on the pico- to nanosecond time scale.

Exploring the Formation and the Structure of Synaptobrevin Oligomers in a Model Membrane. - Han, Jing; Pluhackova, Kristyna; Böckmann, Rainer (Biophysical Journal, 2016)
SNARE complexes have been shown to act cooperatively to enable the synaptic vesicle fusion in neuronal transmission at millisecond timescale. It has previously been suggested that the oligomerization of SNARE complexes required for cooperative action in fusion is mediated by interactions between transmembrane domains (TMDs). We study the oligomerization of synaptobrevin TMD using ensembles of molecular dynamics (MD) simulations at coarse-grained resolution for both the wild-type (WT) and selected mutants. Trimerization and tetramerization of the sybII WT and mutants displayed distinct kinetics depending both on the rate of dimerization and the availability of alternative binding interfaces. Interestingly, the tetramerization kinetics and propensity for the sybII W89A-W90A mutant was significantly increased as compared with the WT; the tryptophans in WT sybII impose sterical restraints on oligomer packing, thereby maintaining an appropriate plasticity and accessibility of sybII to the binding of its cognate SNARE partners during membrane fusion. Higher-order oligomeric models (ranging from pentamer to octamer), built by incremental addition of peptides to smaller oligomers, revealed substantial stability and high compactness. These larger sybII oligomers may induce membrane deformation, thereby possibly facilitating fast fusion exocytosis.

Extension of the LOPLS-AA Force Field for Alcohols, Esters, and Monoolein Bilayers and its Validation by Neutron Scattering Experiments. - Pluhackova, Kristyna; Morhenn, Humphrey; Lautner, Lisa; Lohstroh, Wiebke; Nemkovski, Kirill; Unruh, Tobias; Böckmann, Rainer (Journal of Physical Chemistry B, 2015)
The recently presented LOPLS-AA all-atom force field for long hydrocarbon chains, based on the OPLS-AA force field, was extended to alcohols, esters, and glyceryl monooleate (GMO) lipids as a model lipid. Dihedral angles were fitted against high level ab initio calculations, and ester charges were increased to improve their hydration properties. Additionally, the ester Lennard-Jones parameters were readjusted to reproduce experimental liquid bulk properties, densities, and heats of vaporization. This extension enabled the setup of LOPLS-AA parameters for GMO molecules. The properties of the lipid force field were tested for the liquid-crystalline phase of a GMO bilayer. The obtained area per lipid for GMO is in good agreement with experiment. Additionally, the lipid dynamics on the subpicosecond to the nanosecond time scale is in excellent agreement with results from time-of-flight (TOF) quasielastic neutron scattering (QENS) experiments on a multilamellar monoolein system, enabling here for the first time the critical evaluation of the short-time dynamics obtained from a molecular dynamics simulation of a membrane system.

Going backward: A flexible geometric approach to reverse transformation from coarse grained to atomistic models - Wassenaar, Tsjerk; Pluhackova, Kristyna; Böckmann, Rainer; Marrink, Siewert-Jan; Tieleman, Peter (Journal of Chemical Theory and Computation, 2014)
The conversion of coarse-grained to atomistic models is an important step in obtaining insight about atomistic scale processes from coarse-grained simulations. For this process, called backmapping or reverse transformation, several tools are available, but these commonly require libraries of molecule fragments or they are linked to a specific software package. In addition, the methods are usually restricted to specific molecules and to a specific force field. Here, we present an alternative method, consisting of geometric projection and subsequent force-field based relaxation. This method is designed to be simple and flexible, and offers a generic solution for resolution transformation. For simple systems, the conversion only requires a list of particle correspondences on the two levels of resolution. For special cases, such as nondefault protonation states of amino acids and virtual sites, a target particle list can be specified. The mapping uses simple building blocks, which list the particles on the different levels of resolution. For conversion to higher resolution, the initial model is relaxed with several short cycles of energy minimization and position-restrained MD. The reconstruction of an atomistic backbone from a coarse-grained model is done using a new dedicated algorithm. The method is generic and can be used to map between any two particle based representations, provided that a mapping can be written. The focus of this work is on the coarse-grained MARTINI force field, for which mapping definitions are written to allow conversion to and from the higher-resolution force fields GROMOS, CHARMM, and AMBER, and to and from a simplified three-bead lipid model. Together, these offer the possibility to simulate mesoscopic membrane structures, to be transformed to MARTINI and subsequently to an atomistic model for investigation of detailed interactions. The method was tested on a set of systems ranging from a simple, single-component bilayer to a large protein-membrane-solvent complex. The results demonstrate the efficiency and the efficacy of the new approach. © 2013 American Chemical Society.

High-throughput simulations of dimer and trimer assembly of membrane proteins. The DAFT approach - Wassenaar, Tsjerk; Pluhackova, Kristyna; Moussatova, Anastassiia; Sengupta, Durba; Marrink, Siewert-Jan; Tieleman, Peter; Böckmann, Rainer (Journal of Chemical Theory and Computation, 2015)
Interactions between membrane proteins are of great biological significance and are consequently an important target for pharmacological intervention. Unfortunately, it is still difficult to obtain detailed views on such interactions, both experimentally, where the environment hampers atomic resolution investigation, and computationally, where the time and length scales are problematic. Coarse grain simulations have alleviated the later issue, but the slow movement through the bilayer, coupled to the long life times of nonoptimal dimers, still stands in the way of characterizing binding distributions. In this work, we present DAFT, a Docking Assay For Transmembrane components, developed to identify preferred binding orientations. The method builds on a program developed recently for generating custom membranes, called insane (INSert membrANE). The key feature of DAFT is the setup of starting structures, for which optimal periodic boundary conditions are devised. The purpose of DAFT is to perform a large number of simulations with different components, starting from unbiased noninteracting initial states, such that the simulations evolve collectively, in a manner reflecting the underlying energy landscape of interaction. The implementation and characteristic features of DAFT are explained, and the efficacy and relaxation properties of the method are explored for oligomerization of glycophorin A dimers, polyleucine dimers and trimers, MS1 trimers, and rhodopsin dimers. The results suggest that, for simple helices, such as GpA and polyleucine, in POPC/DOPC membranes series of 500 simulations of 500 ns each allow characterization of the helix dimer orientations and allow comparing associating and nonassociating components. However, the results also demonstrate that short simulations may suffer significantly from nonconvergence of the ensemble and that using too few simulations may obscure or distort features of the interaction distribution. For trimers, simulation times exceeding several microseconds appear needed, due to the increased complexity. Similarly, characterization of larger proteins, such as rhodopsin, takes longer time scales due to the slower diffusion and the increased complexity of binding interfaces. DAFT and its auxiliary programs have been made available from http://cgmartini.nl/, together with a working example.

Interleaflet Interaction in Phase Separated Asymmetric Lipid Bilayers - Saitov, Ali; Pluhackova, Kristyna; Galimzyanov, Timur R.; Böckmann, Rainer; Akimov, Sergey A.; Pohl, Peter (BIOPHYSICAL JOURNAL, 2020)
CRIS-Team WoS Importer:2020-03-13

Lipid Dynamics in Membranes Slowed Down by Transmembrane Proteins - Ebersberger, Lisa; Schindler, Torben; Kirsch, Sonja; Pluhackova, Kristyna; Schambony, Alexandra; Seydel, Tilo; Böckmann, Rainer; Unruh, Tobias (Frontiers in Cell and Developmental Biology, 2020)
Lipids and proteins, as essential components of biological cell membranes, exhibit a significant degree of freedom for different kinds of motions including lateral long-range mobility. Due to their interactions, they not only preserve the cellular membrane but also contribute to many important cellular functions as e.g., signal transport or molecular exchange of the cell with its surrounding. Many of these processes take place on a short time (up to some nanoseconds) and length scale (up to some nanometers) which is perfectly accessible by quasielastic neutron scattering (QENS) experiments and molecular dynamics (MD) simulations. In order to probe the influence of a peptide, a transmembrane sequence of the transferrin receptor (TFRC) protein, on the dynamics of 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) large unilamellar vesicles (LUVs) on a nanosecond time scale, high-resolution QENS experiments and complementary MD simulations have been utilized. By using different scattering contrasts in the experiment (chain-deuterated lipids and protonated lipids, respectively), a model could be developed which allows to examine the lipid and peptide dynamics separately. The experimental results revealed a restricted lipid lateral mobility in the presence of the TFRC transmembrane peptides. Also the apparent self-diffusion coefficient of the lateral movement of the peptide molecules could be determined quantitatively for the probed short-time regime. The findings could be confirmed very precisely by MD simulations. Furthermore, the article presents an estimation for the radius of influence of the peptides on the lipid long-range dynamics which could be determined by consistently combining results from experiment and simulation.
CRIS-Team WoS Importer:2020-11-27

Molecular dynamics simulations of membrane proteins. - Pluhackova, Kristyna; Wassenaar, Tsjerk; Böckmann, Rainer (Methods in Molecular Biology, 2013)
Molecular dynamics simulations are a powerful tool for complementing experimental studies, providing insights in biological processes at the molecular and atomistic level, at timescales from picoseconds to microseconds. Simulations are useful for testing hypotheses and can provide explanations for experimental observations as well as suggestions for further experiments. This does require that the simulation setup allows assessment of the question addressed. For example, it is evident that for simulation of a protein in its functional state the protein model and the environment have to mimic the biological situation as close as possible. In this chapter, a general strategy is presented for setting up and running simulations of membrane proteins of known structure in biological membranes of diverse composition and size.

Optimization of the OPLS-AA force field for long hydrocarbons - Siu, Shirley Weng In; Pluhackova, Kristyna; Böckmann, Rainer (Journal of Chemical Theory and Computation, 2012)
The all-atom optimized potentials for liquid simulations (OPLS-AA) force field is a popular force field for simulating biomolecules. However, the current OPLS parameters for hydrocarbons developed using short alkanes cannot reproduce the liquid properties of long alkanes in molecular dynamics simulations. Therefore, the extension of OPLS-AA to (phospho)lipid molecules required for the study of biological membranes was hampered in the past. Here, we optimized the OPLS-AA force field for both short and long hydrocarbons. Following the framework of the OPLS-AA parametrization, we refined the torsional parameters for hydrocarbons by fitting to the gas-phase ab initio energy profiles calculated at the accurate MP2/aug-cc-pVTZ theory level. Additionally, the depth of the Lennard-Jones potential for methylene hydrogen atoms was adjusted to reproduce the densities and the heats of vaporization of alkanes and alkenes of different lengths. Optimization of partial charges finally allowed to reproduce the gel-to-liquid-phase transition temperature for pentadecane and solvation free energies. It is shown that the optimized parameter set (L-OPLS) yields improved hydrocarbon diffusion coefficients, viscosities, and gauche-trans ratios. Moreover, its applicability for lipid bilayer simulations is shown for a GMO bilayer in its liquid-crystalline phase. © 2012 American Chemical Society.

Spontaneous adsorption of coiled-coil model peptides K and E to a mixed lipid bilayer. - Pluhackova, Kristyna; Wassenaar, Tsjerk; Kirsch, Sonja; Böckmann, Rainer (Journal of Physical Chemistry B, 2015)
A molecular description of the lipid-protein interactions underlying the adsorption of proteins to membranes is crucial for understanding, for example, the specificity of adsorption or the binding strength of a protein to a bilayer, or for characterizing protein-induced changes of membrane properties. In this paper, we extend an automated in silico assay (DAFT) for binding studies and apply it to characterize the adsorption of the model fusion peptides E and K to a mixed phospholipid/cholesterol membrane using coarse-grained molecular dynamics simulations. In addition, we couple the coarse-grained protocol to reverse transformation to atomistic resolution, thereby allowing to study molecular interactions with high detail. The experimentally observed differential binding of the peptides E and K to membranes, as well as the increased binding affinity of helical over unstructered peptides, could be well reproduced using the polarizable Martini coarse-grained (CG) force field. Binding to neutral membranes is shown to be dominated by initial binding of the positively charged N-terminus to the phospholipid headgroup region, followed by membrane surface-aligned insertion of the peptide at the interface between the hydrophobic core of the membrane and its polar headgroup region. Both coarse-grained and atomistic simulations confirm a before hypothesized snorkeling of lysine side chains for the membrane-bound state of the peptide K. Cholesterol was found to be enriched in peptide vicinity, which is probably of importance for the mechanism of membrane fusion. The applied sequential multiscale method, using coarse-grained simulations for the slow adsorption process of peptides to membranes followed by backward transformation to atomistic detail and subsequent atomistic simulations of the preformed peptide-lipid complexes, is shown to be a versatile approach to study the interactions of peptides or proteins with biomembranes.

Structural Model of the mIgM B-Cell Receptor Transmembrane Domain From Self-Association Molecular Dynamics Simulations - Frieß, Mario; Pluhackova, Kristyna; Böckmann, Rainer (Frontiers in Immunology, 2018)
Antigen binding to B-cell antigen receptors (BCRs) followed by signaling initiates the humoral immune response. The signaling is intimately coupled to nanoclustering of BCRs and their sorting to specific membrane domains, a process that is ruled by interactions between the BCR transmembrane domain and lipids. While the structure of the extracellular domains of BCRs has been resolved, little is known about the configuration of the constituting four immunoglobulin domains spanning the membrane. Here, we modeled the structure of the transmembrane (TM) domain of the IgM B-cell receptor using self-assembly coarse-grained molecular dynamics simulations. The obtained quaternary structure was validated against available experimental data and atomistic simulations. The IgM-BCR-TM domain configuration shows a 1:1 stoichiometry between the homodimeric membrane-bound domain of IgM (mIgM) and a Ig-alpha/Ig-beta heterodimer. The mIgM homodimer is based on an asymmetric association of two mIgM domains. We show that a specific site of the Ig-alpha/Ig-beta heterodimer is responsible for the association of IgM-BCRs with lipid rafts. Our results further suggest that this site is blocked in small-sized IgM-BCR clusters. The BCR TM structure provides a molecular basis for the previously suggested dissociation activation model of B-cell receptors. Self-assembly molecular dynamics simulations at the coarse-grained scale here proved as a versatile tool in the study of receptor complexes.
Keywords: B-cell receptor; transmembrane domain; nanodomains; self-assembly; molecular dynamics simulations; coarse-grained simulations; dissociation activation model

Synaptobrevin transmembrane domain determines the structure and dynamics of the SNARE motif and the linker region. - Han, Jing; Pluhackova, Kristyna; Bruns, Dieter; Böckmann, Rainer (BBA - Biochimica et Biophysica Acta, 2016)
The vesicular protein synaptobrevin II (sybII) constitutes a central component of the SNARE complex, which mediates vesicle fusion in neuronal exocytosis. Previous studies revealed that the transmembrane domain (TMD) of sybII is playing a critical role in the fusion process and is involved in all distinct fusion stages from priming to fusion pore opening. Here, we analyzed sequence-dependent effects of sybII and of mutants of sybII on both structure and flexibility of the protein and the interactions with a phospholipid bilayer by means of microsecond atomistic simulations. The sybII TMD was found to direct the folding of both the juxtamembrane helix and of the connecting linker and thus to influence both the intrinsic helicity and flexibility. Fusion active peptides revealed two helical segments, one for the juxtamembrane region and one for the TMD, connected by a flexible linker. In contrast, a fusion-inactive poly-leucine TMD mutant assumes a structure with a comparably rigid linker that is suggested to hinder the formation of the trans-SNARE complex during fusion. Kinking of the TMD at the central glycine together with anchoring of the TMD via conserved tryptophans and a lysine in position 94 likely yields an enhanced flexibility of sybII for different membrane thickness. All studied peptides were found to deform the outer membrane layer by altering the lipid head group orientation, causing partial membrane dehydration and enhancing lipid protrusions. These effects weaken the integrity of the outer membrane layer and are attributed mainly to the highly charged linker and JM regions of sybII.

Synaptobrevin Transmembrane Domain Dimerization Studied by Multiscale Molecular Dynamics Simulations - Han, Jing; Pluhackova, Kristyna; Wassenaar, Tsjerk; Böckmann, Rainer (Biophysical Journal, 2015)
Synaptic vesicle fusion requires assembly of the SNARE complex composed of SNAP-25, syntaxin-1, and synaptobrevin-2 (sybII) proteins. The SNARE proteins found in vesicle membranes have previously been shown to dimerize via transmembrane (TM) domain interactions. While syntaxin homodimerization is supposed to promote the transition from hemifusion to complete fusion, the role of synaptobrevin's TM domain association in the fusion process remains poorly understood. Here, we combined coarse-grained and atomistic simulations to model the homodimerization of the sybII transmembrane domain and of selected TM mutants. The wild-type helix is shown to form a stable, right-handed dimer with the most populated helix-helix interface, including key residues predicted in a previous mutagenesis study. In addition, two alternative binding interfaces were discovered, which are essential to explain the experimentally observed higher-order oligomerization of sybII. In contrast, only one dimerization interface was found for a fusion-inactive poly-Leu mutant. Moreover, the association kinetics found for this mutant is lower as compared to the wild-type. These differences in dimerization between the wild-type and the poly-Leu mutant are suggested to be responsible for the reported differences in fusogenic activity between these peptides. This study provides molecular insight into the role of TM sequence specificity for peptide aggregation in membranes.

The Multifaceted Role of SNARE Proteins in Membrane Fusion. - Han, Jing; Pluhackova, Kristyna; Böckmann, Rainer (Frontiers in Physiology, 2017)
Membrane fusion is a key process in all living organisms that contributes to a variety of biological processes including viral infection, cell fertilization, as well as intracellular transport, and neurotransmitter release. In particular, the various membrane-enclosed compartments in eukaryotic cells need to exchange their contents and communicate across membranes. Efficient and controllable fusion of biological membranes is known to be driven by cooperative action of SNARE proteins, which constitute the central components of the eukaryotic fusion machinery responsible for fusion of synaptic vesicles with the plasma membrane. During exocytosis, vesicle-associated v-SNARE (synaptobrevin) and target cell-associated t-SNAREs (syntaxin and SNAP-25) assemble into a core trans-SNARE complex. This complex plays a versatile role at various stages of exocytosis ranging from the priming to fusion pore formation and expansion, finally resulting in the release or exchange of the vesicle content. This review summarizes current knowledge on the intricate molecular mechanisms underlying exocytosis triggered and catalyzed by SNARE proteins. Particular attention is given to the function of the peptidic SNARE membrane anchors and the role of SNARE-lipid interactions in fusion. Moreover, the regulatory mechanisms by synaptic auxiliary proteins in SNARE-driven membrane fusion are briefly outlined.